THE RELATIONSHIP OF FAMILY SUPPORT WITH BABY BLUES SYNDROME IN POST PARTICULAR MOTHERS IN THE SIMOREJO REGION, SIMOMULYA DISTRICT, SURABAYA CITY - Mahundingan, Rosari Oktaviana; Andriani, Dewi (Universitas Airlangga, 2024)
Introduction: Women who have just given birth experience physical and psychological changes. The release period is a time when mothers try to take over responsibility. Psychological changes occur in various periods, namely Taking In, Taking Holding, and Letting Go. The psychological changes of mothers who have just given birth require support from the family to adjust. Postpartum mothers in avoiding Baby Blues Syndrome are also influenced by very important family support. The aim of this research is to determine the relationship between family support and the occurrence of Baby Blues Syndrome in postpartum mothers Methods: The research is a cross-sectional research approach, using a sample of 25 postpartum mothers in the Simorejo area, Simomulya District, Surabaya City with a consecutive sampling technique. Analysis of this research data used the Spearman Rho test. Results: The proportion with high family support (57.9%) with a P value (0.000). The meaning that if family support is high then Baby Blues Syndrome will not occur. Conclusions: The average level of family support received was 56%, so this research is expected to increase knowledge for mothers after giving birth by paying attention to family support to avoid the occurrence of Baby Blues Syndrome.